Satisfaction levels of patients visiting primary health care centers in border areas of Jammu division - Teli, Prabhakar; Oak, Shailesh; Yadav, Arun Kumar; Grewal, Vikram Singh (International Journal Of Community Medicine And Public Health, 2019)
Background: Patient satisfaction surveys are one of the most important feedback systems for any hospital to understand patient concern and take necessary corrective measures. The study was done in primary health centers in border areas of Jammu division to know the satisfaction among the patient and describe their socio-demographic profile. Methods: Study was cross-sectional questionnaire based study conducted among the inpatient of the primary health center, Paragwal from 01 July 2018 to 30 November 2018. Data was collected using a pre-tested questionnaire and entered in an excel sheet and analysed using SPSS 20. Results: A total of 110 respondents participated in the group. The mean age of the study subjects was 43.4±9.7 years and majority (86%) of the respondents was married, higher proportions of males (71%) and majority subjects (77%) were illiterate. According to Kuppuswamy scale, 66% of the study subjects belong to low socio-economic status (SES). There was no statistical significant association of socio-economic status, age, literacy. Female gender was associated with satisfaction regarding explanation of illness. Conclusions: In the present study, we found that majority of the participant were satisfied. However, the areas like congestion and time management needs improvement.